Expedition Service Product Development Strategy with Quality Function Deployment Method - Indah Nurlina; Septin Puji Astuti; Azis Slamet Wiyono (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2020)
This study assesses the quality of Express Post service provided by PT. Pos Indonesia with Quality Function Deployment Method (QFD). Approximately 90 customers of Express Post in Boyolali were selected through systematic sampling to gather their opinions. In the meantime, PT Post Indonesia’s Jakarta Central Office’s Research and Development Department is involved to collect technical responses or activites. This study has identified 12 attributes of Express Post that require improvement. To solve the problems related to those attributes, this study has identified training on Express Post service standard operating procedure for new employees as the priority activity to be undertaken by PT. Pos Indonesia since it has the most significant influence on the quality of Express Post. In addition, the study also suggests two other technical responses to be taken into consideration including ensuring service cut of time of and ensuring delivery reception not disrupting the service cut off time.